Digital Identities and Study Abroad: Teaching Intercultural Competence through Social Media Literacy - Annie McNeill Gibson; Emily Capdeville (Journal of Global Initiatives, 2019)
Social media platforms are contemporary spaces where selves are revealed and exposed in reciprocity. By imagining digital communication, technology use, and online representation in the same vein as we discuss the experiences of the physical self, the ability to adapt across cultures becomes a skill to hone online as well as in person. As such, digital media is a prime learning tool that practitioners in the field can utilize to reach their target student population no matter their physical location and during each phase of the study abroad process. In this way, study abroad offices can fulfill a mission that goes beyond the logistics of travel in order to concentrate attention on the development of student intercultural competencies.